Faktor-Faktor yang Berhubungan dengan Tingkat Depresi Lansia: The Relationship Between Social Support and Depression Levels Among Elderly People in Nursing Homes - Hulu, Vera Kristina (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Increasing life expectancy has led to an increase in the number of older people, with the risk of psychological problems such as depression. Depression in the elderly, especially those living in institutions, is a serious concern because it is related to conditions of social isolation, loss of spouse, and low activity involvement. This study aims to determine the factors associated with the level of elderly depression at the Binjai Cengkeh Turi Elderly Home. This study used a descriptive quantitative approach with a population of 30 elderly over 65 years old as a sample. Data collection was carried out through the Geriatric Depression Scale (GDS) questionnaire consisting of 15 items, and relationship analysis using the Spearman correlation test. The results showed that the majority of respondents were aged 65-75 years, female, and unmarried. A total of 93.33% of the elderly experienced symptoms of depression, with most of them being at a moderate level of depression. The level of social support was mostly in the moderate category (96.67%). Statistical tests showed no significant relationship between age and social support on the level of depression. This study concluded that although the majority of elderly people showed symptoms of depression, there was no significant relationship between social support and age with the level of depression. It is recommended that further research consider other psychosocial variables such as motivation, family relationships, and physical health conditions.